Immobilization of enzymes on porous silicas - benefits and challenges - Hartmann, Martin; Kostrov, Xenia (Chemical Society Reviews, 2013)
Porous silica materials have extensively been used for the immobilization of enzymes aiming at their use as biocatalysts or biosensors. This tutorial review will discuss the benefits and challenges of different immobilization techniques and will provide references to recent papers for further reading. Moreover, novel trends and unsolved problems will be introduced.